Interfacing sensors to the ibm-pc - Tompkins, Willis J.; Webster, John G. (Englewood Cliff Prentice Hall, 1988)
This volume thoroughly explores all the principles and techniques necessary for connecting any type of sensor to the IBM PC or equivalent computers -- e.g., sensors, transducers, data conversion, and interface techniques.